Highly Sensitive Small Pressure Monitoring Using Hyperelastic Silicone-Cladding/Silica-Core Composite Optical Fiber - Bin Zhou; Liang Wang; Lin Htein; Zhengyong Liu; Xiaolu Chen; Hwa-Yaw Tam; Chao Lu (IEEE Photonics Journal, 2017)
We have fabricated a composite optical fiber with hyperelastic silicone cladding and silica core, and demonstrated a simple and highly sensitive pressure sensor based on the light coupling between two such composite fibers twisted together. The hyperelastic silicone has very low Young's modulus which makes the fiber deformation easier even under small pressure and hence improves the light coupling and pressure sensitivity. Both simulation and experiment show that the light coupling based pressure sensor using the composite fibers is very sensitive to small pressure (e.g., several newtons) compared with those using conventional silica fibers and polymethyl methacrylate resin polymer fibers, which almost have no response to small pressure. With excellent sensitivity and fast response time ( $\ll 1\;{\rm{s}}$ ), both static and dynamic side pressure have been successfully detected. The sensing configuration is simple without any complicated structures and would be a cost-effective candidate for highly sensitive small pressure monitoring.